ASSOCIATION BETWEEN CORONARY HEART DISEASE AND GALLSTONE DISEASE (EPIDEMIOLOGICAL STUDY) - I. N. Grigorieva; Yu. I. Ragino; T. I. Romanova; S. K. Malyutina (Атеросклероз, 2019)
The aim of the study was to evaluate in the epidemiological study the possible association of coronary heart disease (CHD) and gallstone disease (GSD) in women aged 25–64 years and in men aged 35-54 years, and assess the possible impact on it of certain conventional risk factors (body mass index (BMI), dyslipoproteinemia (DLP), the presence of arterial hypertension (AH) and of diabetes mellitus (DM) type 2) in women. In the frame of the WHO “MONICA” programs it was shown, that among the unorganized urban men population (n = 399) there was no significant relationship between the presence of «definite» IHD and GSD: OR = 0.8 (95 % CI 0.1–6.4, p = 0.8). Among the unorganized urban women population (n = 870) a direct association of GSD with a «definite» coronary artery disease was established: OR = 2.0 (95 % CI 1.1–3.4; p < 0.05), which did not depend on the presence or absence of AH (OR = 1.8; 95 % CI 1.01–3.1; p < 0.05), DLP (OR = 1.9; 95 % CI 1.1–3.6; p < 0,05) or DM type 2 (OR = 1.8; 95 % CI 1.03–3.6; p < 0.05), but disappeared when age and BMI were included in the analysis (OR = 1.5; 95 % CI 0,9–2.7; p > 0.05 and OR = 1.6; 95 % CI 0.9–2.9; p > 0.05, respectively).